A Spatial Mapping of Children's Toothache Prevalence and Its Determinants - Hariyani, Ninuk; Laisyaina, Defita Ayu; Kuswanda, Crisna Tri; Kamilah, Tsaniya; Palupi, Retno; Sosiawan, Agung; Sengupta, Kaushik (Indonesian Journal of Dental Medicine, 2025)
Background: Toothache is the most common oral pain and has been confirmed as a public health problem. World Health Organization (WHO) stated that oral health problem impacts 90% of pre-adolescent, ranging from the feeling of distressing pain, nutritional intake disturbance, to the extent of school absence. Geospatial Information System (GIS) is a method to describe a data in a spatial geographic mapping, it can be a valuable tool to explore the relationships between health and its determinant factors, and also show the locations where the problem occurs. Purpose: To describe the geospatial mapping of toothache prevalence and its determinant behavioural factors among Indonesian children. Methods: It is a secondary data analysis of the 5th wave of Indonesian Family Life Survey (IFLS) data. The 7,010 respondents’ data from children aged 5-15 years old were analysed and mapped using Quantum GIS. Geospatial data mapping was conducted by inserting toothache prevalence and its determinant factors to the geographical map. Results: Based on the mapping, there are a consistent pattern of the prevalence, in which South Sulawesi and South Kalimantan provinces have the very high number in toothache prevalence, bad sugar consumption behavior and bad toothbrushing behavior. Conclusions: This study showed the prevalence and distribution of toothache and its behavioural determinants among children age 5-15 years old in Indonesia, across provinces. Therefore, toothache among Indonesian children is an oral health problem that needs attention and intervention.